2020
DOI: 10.1177/000313482008600335
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Dilemma: Skip Metastasis in Papillary Thyroid Cancer

Abstract: The frequency, pattern, and predictive factors for skip LN metastasis in patients with papillary thyroid carcinoma (PTC) remain controversial. In this study, we evaluated predictive factors of skip LN metastasis in these patients. We reviewed the medical records of 68 PTC patients who underwent total thyroidectomy, central neck dissection, and lateral neck dissection at the initial operation. The relationships between skip LN metastasis and clinicopathologic factors were analyzed. After careful examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Older age is a risk factor for both PTC [17][18][19] and LLNM. 20,21 Wang et al concluded that age ≥55 years was an independent risk factor for SLNM, which is consistent with the findings of this study. 13 There is still controversy regarding the size and invasiveness of tumors in SLNM patients.…”
Section: Discussionsupporting
confidence: 92%
“…Older age is a risk factor for both PTC [17][18][19] and LLNM. 20,21 Wang et al concluded that age ≥55 years was an independent risk factor for SLNM, which is consistent with the findings of this study. 13 There is still controversy regarding the size and invasiveness of tumors in SLNM patients.…”
Section: Discussionsupporting
confidence: 92%
“…In the univariate and multivariate analyses, the rate of skip metastasis was significantly higher in patients with a tumour size ≤10 mm (P = 0.033), upper tumour location (P = 0.006) and fewer CLNDs (P = 0.005). Previously, many studies ( 18 , 20 , 23 ) have reported that skip lymph node metastasis is associated with tumour size, and skip metastasis is often found to be more common in PTC patients with a tumour size ≤1 cm. Several of these studies ( 15 , 24 , 25 ) found that the location of the tumour in the upper pole is one of the independent risk factors for the development of skip metastasis in patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is one of the most common malignant tumors in the endocrine system 1 and has registered an annual growth rate of 2% in recent decades. 2 Papillary thyroid cancer (PTC) is the most common type of malignant thyroid tumor, with more than 10 known subtypes that account for 85-90% of all thyroid malignancies. 3,4 Fortunately, most PTCs are relatively inert and the 10-year survival rate for patients undergoing a glandectomy or total thyroidectomy plus I131 treatment is greater than 95%.…”
Section: Introductionmentioning
confidence: 99%